2021
DOI: 10.1108/lthe-08-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Memorization practice and academic success in Saudi undergraduate students

Abstract: PurposeIn the present study, the authors examined whether academic performance [grade point average (GPA)] can be predicted by self-reported frequency of memorization and recitation, verbatim memory performance, and self-efficacy in a sample of college students from Saudi Arabia.Design/methodology/approachStudents' verse memory, word memory, experience with memorization and recitation, as well as general self-efficacy were measured. GPA was provided by the Office of the Registrar.FindingsVerbatim memory perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The lack of a contribution of self-efficacy to academic performance is consistent with the findings of Choi (2005) but inconsistent with those of Naderi et al (2018) and Lane and Lane (2001) who reported a moderate contribution. An earlier study by Pilotti et al (2022a), which included a sample of Saudi college students, also failed to find a significant relationship between the two variables. One possible account for our finding comes from Fenning and May (2013) who found that students' general selfefficacy was positively related to their academic performance in high school but not in college.…”
Section: Discussionmentioning
confidence: 79%
“…The lack of a contribution of self-efficacy to academic performance is consistent with the findings of Choi (2005) but inconsistent with those of Naderi et al (2018) and Lane and Lane (2001) who reported a moderate contribution. An earlier study by Pilotti et al (2022a), which included a sample of Saudi college students, also failed to find a significant relationship between the two variables. One possible account for our finding comes from Fenning and May (2013) who found that students' general selfefficacy was positively related to their academic performance in high school but not in college.…”
Section: Discussionmentioning
confidence: 79%
“…To this end, consider that in the present study, late submissions of the first assignment, which were measured only in the UR course, were infrequent (4.60%), often due to circumstances beyond students' control (e.g., death of a family member), had supporting documentation, and were unrelated to any of the procrastination dimensions, r s ≤ −.05, ns . A possible explanation for the null predictive validity of the self‐efficacy measure may be students' difficulties in assessing it, as demonstrated by the limited range of variability of the self‐efficacy ratings with most scores being above the neutral point (Pilotti, Alkuhayli, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the null predictive validity of the self-efficacy measure may be students' difficulties in assessing it, as demonstrated by the limited range of variability of the self-efficacy ratings with most scores being above the neutral point (Pilotti, Alkuhayli, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%